Analisis Usability Sistem E-Voting Pemilihan Ketua dan Wakil Ketua OSIS dengan Metode Think Aloud - Fajar Husain Asyari; Ellen Proborini; Sholihul Ibad (Jurnal Teknologi Terpadu, 2026)
The election of the OSIS (Student Council) chairman and vice-chairman is an important school agenda that requires a fast, accurate, and transparent voting process. With the advancement of information technology, e-voting systems have become a modern solution, but their success strongly depends on the system's usability. This study aims to evaluate the usability level of the e-voting system for the election of the OSIS (Student Council) president and vice-president using the Think Aloud method. The evaluation involved ten student respondents as the system’s target users, who were asked to complete six task scenarios—from entering the token to logging out—while verbalizing their thoughts and difficulties. The results showed that 90% of respondents successfully completed task scenarios T1–T5, while 60% encountered difficulties in task T6 (logging out). Based on the severity rating analysis, three main issues were identified: slow response time (score 4, critical), unclear navigation (score 3, major), and confusing input forms (score 3, major). Overall, the system achieved a task completion rate of 93.3% with an average completion time of 38 seconds per task. These results indicate that the e-voting system demonstrates good usability but requires improvements in navigation, system performance, and input guidance to enhance user experience. The Think Aloud method proved effective in directly identifying usability issues from the user perspective.